The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.17221/6604-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in lipids of carp (Cyprinus carpio) tissues

Abstract: The content of fat in carp (Cyprinus carpio) tissue was evaluated throughout one year. The following tissues were evaluated: skeletal muscle, soft roe, hard roe, fat tissue, and hepatopancreas. Respective fatty acids were determined using gas liquid chromatography (GLC). The highest content of valuable polyunsaturated acids, like eicosahexaenoic acid, was found in soft roe and in skeletal muscle during summer, in hepatopancreas during spring, in hard roe during fall. The content of eicosahexaenoic acid in hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 4 publications
6
25
1
Order By: Relevance
“…Guler et al (2008) found oleic acid and palmitoleic to be a primary and secondary MUFA in the carp in all seasons (15.1-20.3 and 5.1-13.2%, respectively). The previous research showed similar results in carp muscle during the four seasons (Kmínková et al 2001). Oleic acid was significantly higher in the farmed carp than in the wild one.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Guler et al (2008) found oleic acid and palmitoleic to be a primary and secondary MUFA in the carp in all seasons (15.1-20.3 and 5.1-13.2%, respectively). The previous research showed similar results in carp muscle during the four seasons (Kmínková et al 2001). Oleic acid was significantly higher in the farmed carp than in the wild one.…”
Section: Discussionsupporting
confidence: 76%
“…MUFA contents of carp fillets were higher than those of SFA in spring, autumn, and winter, 35.7, 37.3, and 41.1%, respectively. According to the results of Kmínková et al (2001), MUFA contents of carp fillets were higher than those of SFA and PUFA in all seasons, while PUFA contents were lower than those of SFA. Our data showed that a high level of oleic acid increased MUFA content in all seasons.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations